Tonk Sándor Emlékkonferencia Kolozsváron - Szögi, László (Gerundium, 2019)
Memorial Conference for Sándor Tonk at Kolozsvár/Cluj. On 5th and 6th of October 2018 colleagues, friends and admirers remembered for the early died Mr. Sándor Tonk who was an excellent representative of the Transylvanian Hungarian histography. The memorial conference was organized by the Research Institute of the Transylvanian Museum Society, Sapientia Hungarian University of Transylvania, and Department of the Hungarian History of Babeş-Bolyai University. Those researchers of the above mentioned institutes and Hungarian historians took part at the conference whose research matter was close to the activity of Sándor Tonk or to the Transylvanian histography. The essay below reflects the summarized lectures of the conference and states that in Transylvania a new generation of historians has grown up which continues the work of Sándor Tonk and other historians and develops the Hungarian histography with their new conclusions.